A longitudinal study investigating the association between social maturity, social preference and children’s perceptions of their playfulness - Rianne L. van de Weitgraven; Brenda R. J. Jansen; Tycho J. Dekkers; Elian Fink (Scientific Reports)
Abstract Children’s playfulness is associated with increased social skills and positively predicts children’s later prosocial skills. Social skills become increasingly important as children enter formal schooling. To understand the role of playfulness in children’s social-emotional development during the first years of school, this three time-point longitudinal study aimed to explore the reciprocal longitudinal associations between children’s self-reported playfulness, teacher-reported social maturity, and peer-reported social preference over time. The sample consisted of 172 children (99 boys [58%], majority White [79.5%]) from England who were first seen at age 5 (M = 63 months, SD = 3.86) and then at ages 6 (M = 73 months, SD = 4.53) and 7 (M = 81 months, SD = 4.69). Findings showed robust longitudinal stability in children’s self-reported playfulness across the three time-points. Children’s own perceptions of their playfulness at age 7 were predicted by teacher’s views of their social maturity and peer-ratings of social preference. As playfulness both drives behaviour and reflects how others judge a child’s behaviour, it is important to consider playfulness when trying to protect and promote children’s social-emotional competencies. Given the rise in play-based pedagogies, further research is needed to explore the impact of context on these findings.